2003
DOI: 10.1017/s135561770397010x
|View full text |Cite
|
Sign up to set email alerts
|

Left and right basal ganglia and frontal activity during language generation: Contributions to lexical, semantic, and phonological processes

Abstract: fMRI was used to determine the frontal, basal ganglia, and thalamic structures engaged by three facets of language generation: lexical status of generated items, the use of semantic vs. phonological information during language generation, and rate of generation. During fMRI, 21 neurologically normal subjects performed four tasks: generation of nonsense syllables given beginning and ending consonant blends, generation of words given a rhyming word, generation of words given a semantic category at a fast rate (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
115
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 55 publications
11
115
1
Order By: Relevance
“…The posterior regions of the brain activated in these tasks seem to have a relatively greater involvement in retrieval of stored information such as word meaning (BA21) (Demb et al, 1995;McDermott et al, 2003;Poldrack et al, 1999;Shivde & Thompson-Schill, 2004) or sound (BA7/40) (McDermott et al, 2003;Shivde & Thompson-Schill, 2004). Therefore, the findings on our activation maps correlate with the general knowledge about the distribution of the semantic and phonological networks in the brain (Crosson et al, 2003;Devlin et al, 2003;McDermott et al, 2003;Poldrack et al, 1999;Thompson-Schill et al, 1997).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The posterior regions of the brain activated in these tasks seem to have a relatively greater involvement in retrieval of stored information such as word meaning (BA21) (Demb et al, 1995;McDermott et al, 2003;Poldrack et al, 1999;Shivde & Thompson-Schill, 2004) or sound (BA7/40) (McDermott et al, 2003;Shivde & Thompson-Schill, 2004). Therefore, the findings on our activation maps correlate with the general knowledge about the distribution of the semantic and phonological networks in the brain (Crosson et al, 2003;Devlin et al, 2003;McDermott et al, 2003;Poldrack et al, 1999;Thompson-Schill et al, 1997).…”
Section: Discussionsupporting
confidence: 61%
“…However functional deficits are often associated with large lesions and make it difficult to relate specific deficits to specific anatomical regions. Evidence form neuroimaging studies complements the findings from brain damaged patients and makes it possible to identify specific brain areas associated with a specific task (Cabeza & Nyberg, 2000;Crosson et al, 2003;Devlin et al, 2003;Fiez & Petersen, 1998;Martin, 2003;McDermott et al, 2003;Poldrack et al, 1999;Price, 2000;Thompson-Schill et al, 1997). The findings of these studies revealed the existence of a vast network of brain structures that contribute to these language processes, including anterior and posterior, cortical and subcortical brain regions.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Matsumoto et al (2004) suggested a possible indirect pathway between the left IFG and left pSTG/MTG via subcortical regions. An anatomical study in primates showed a pre-SMA projection to the head of the caudate [Inase et al, 1999]; this projection may form the pre-SMA-basal ganglia loop used in word generation [Crosson et al, 2003]. Previous studies based on an inherited speech disorder also suggested that an inferior frontal-basal ganglia loop is a critical neural circuit for speech production [Vargha-Khadem et al, 2005].…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, it is also possible that the observed effect on the right caudate nucleus is related instead to its role in speech production. For instance, Grogan et al (2009) observed that L2 phonemic fluency was associated with gray matter density in bilateral areas of the caudate nucleus, and Crosson et al (2003) observed significant activity in the right caudate nucleus during tasks requiring generation of words.…”
Section: Discussionmentioning
confidence: 99%